The Danger of Traditional Abdominal Massage with Appendicitis; A Long-standing Misunderstanding in Ende, East Nusa Tenggara - Nurmasithah; Sun Parkuseg Siregar (Green Publisher, 2026)
In Southeast Asia, Indonesia has the highest incidence of acute appendicitis, with approximately 5 cases per 1000 individuals. In rural areas, the burden got worse because of locals misconceptions. We noticed that as a part of their cultural beliefs, the patient had a traditional abdominal massage before going to the hospital. This study aims to understand the correlation between conventional abdominal massage with perforated appendicitis and other related complications. This is a retrospective analysis study which identified 47 patients who underwent surgery at Ende General Hospital from January 2020 – September 2023. Univariate and bivariate analysis was performed to describe and analyse the correlation between traditional abdominal massage and complications. This study showed there was a significant correlation between the patients who received traditional abdominal massage with bowel adhesion (OR: 0.071; 95%CI: 0.011 - 0.472; p=0.00), generalized peritonitis (OR: 6.25; 95%CI: 1.53 - 25.41; p= 0.009), perforated appendicitis (OR: 25.6; 95%CI: 4.17 - 156.99; p=0.00), and bowel adhesion (OR: 0.071; 95%CI: 0.011 - 0.472; p=0.00), but not with length of stay (LOS) (OR: 1.030; 95%CI: 0.972 – 1.092; p=0.72). This study found a correlation between traditional abdominal massage and appendicitis complications. Misconception that circulated in this area ended up backfiring on locals, worsening abdominal pain and causing complications. These findings imply that the local government should collaborate with health workers and tribal leaders to raise awareness and clarify inaccurate information.